Improving the scalability of psychological treatments in developing countries: An evaluation of peer-led therapy quality assessment in Goa, India - Singla, Daisy R. (Elsevier Science, 2014)
Psychological treatments delivered by lay therapists, with little or no previous mental health training, have been shown to be effective in treating a range of mental health problems. In low resource settings, the dearth of available experts to assess therapy quality potentially leads to a bottleneck in scaling up lay therapist delivered psychological treatments. Peer-led supervision and the assessment of therapy quality may be one solution to address this barrier. The purpose of this study was two-fold: 1) to assess lay therapist quality ratings compared to expert supervisors in a multisite study where lay therapists delivered two locally developed, psychological treatments for harmful and dependent drinking and severe depression; 2) assess the acceptability and feasibility of peer-led supervision compared to expert-led supervision. We developed two scales, one for each treatment, to compare lay therapist and expert ratings on audio-taped treatment sessions (n = 189). Our findings confirmed our primary hypothesis of increased levels of agreement between peer and expert ratings over three consecutive time periods as demonstrated by a decrease in the differences in mean therapy quality rating scores. This study highlights that lay therapists can be trained to effectively assess each other's therapy sessions as well as experts, and that peer-led supervision is acceptable for lay therapists, thus, enhancing the scalability of psychological treatments in low-resource settings.